Blended Laboratory Design Using Raspberry Pi Pico for Digital Circuits and Systems - Davidson, Zoe C. M.; Dang, Shuping; Vasilakos, Xenofon (IEEE transactions on learning technologies, 2024)
Raspberry Pi Pico, based on chip RP2040, is an easy-to-use development micro-controller board that can provide flexible input/output functions and meets the teaching needs of basic electronics to first-year university undergraduates. This paper presents our blended laboratory design using Raspberry Pi Pico for the course unit Digital Circuits and Systems. Considering the impacts of Coronavirus Disease 2019 (COVID-19) and the reduced number of students attending the in-person laboratory, we provide an alternative approach using an online Raspberry Pi Pico simulator produced by Wokwi for those students who cannot attend the physical laboratory. The entire laboratory is designed by design-based learning (DBL) pedagogical methodology and consists of three dependent sessions. Throughout the three laboratory sessions, first-year undergraduates are expected to understand the basic digital logic and electronic circuits by building a simplified interactive traffic light controller system using Raspberry Pi Pico and Python programming. The intended learning outcomes, full details of the blended laboratory design, and the laboratory design evaluation results are given and discussed in this paper to verify the effectiveness of the blended laboratory design using Raspberry Pi Pico. By analyzing the empirical data collected from laboratory participants, the effectiveness of the proposed blended laboratory design can be well supported, and all intended learning outcomes are successfully achieved subject to the impacts of COVID-19.